Achieving Sustainable Development through the Study of Geography : An Analysis - SINGH, NIDHI (JOURNAL OF INDIAN EDUCATION, 2025)
The Agenda 2030 of Sustainable Development (SD) identifies quality education as its fourth agenda towards reaching SD. This has added an enhanced emphasis on education, which aims towards sustainability. Education, which is regarded not only as means to achieve other goals but also an end in itself, has overarching impact on the well-being of individuals. Study of geography, armed with pedagogy and technological intervention fulfils the agenda four and covers many of the agendas identified towards reaching SD. These include no poverty, zero hunger, good health and well-being, gender equality, and clean water and sanitation, etc. This paper, therefore, tries to bring forward the role of education in general and the study of geography in particular, in reaching out to these goals. The paper attempts to discover the manner in which various concepts of SD can be incorporated in the learning-teaching of geography, primarily at school level. An analysis of the NCERT’s curriculum on the education on SD has also been attempted. An attempt has also been made to devise a course plan and pedagogical integration of the idea of SD at various stages of education to form a synergy with the real world.